Legal and organizational framework for the use of geoweb methods for public participation in spatial planning in Poland: experiences, opinions and challenges - Bąkowska-Waldmann, Edyta; Brudka, Cezary; Jankowski, Piotr (Quaestiones Geographicae, 2018)
Geoweb methods offer an alternative to commonly used public participation methods in spatial planning. This paper discusses two such geoweb methods – geo-questionnaire and geo-discussion in the context of their initial applications within the spatial planning processes in Poland. The paper presents legal and organizational framework for the implementation of methods, provides their development details, and assesses insights gained from their deployment in the context of spatial planning in Poland. The analysed case studies encompass different spatial scales ranging from major cities in Poland (Poznań and Łódź) to suburban municipalities (Rokietnica and Swarzędz in Poznań Agglomeration). The studies have been substantiated by interviews with urban planners and local authorities on the use and value of Geoweb methods in public consultations.